Food hypersensitivity - classification, pathogenesis, diagnosis. What are food allergies? - Jan Dąbrowski; Ilona Gąbka; Weronika Dalmata; Karolina Dębek; Marta Lipiec (Kazimierz Wielki University, 2022)
Introduction: Food hypersensitivity is a pathological, increased and inadequate reaction of the body to a particular substance, the consumption of which can cause various types of body symptoms. Purpose: The purpose of this study is to distinguish different types of hypersensitivity mechanisms, resulting in the introduction of appropriate diagnosis and treatment. Results and conclusions: Food hypersensitivity is becoming an epidemic of the 21st century. This is due to many individual factors as well as environmental pollution. It is important to identify the type of mechanism involved in a given food hypersensitivity and to eliminate the causative factors, or incorporate appropriate treatment. Understanding this forms the basis of therapy. Methods:  Data for the article were retrieved using PubMed setting the time descriptors to 2014-2020.